Pembuatan Aplikasi dan Pelatihan Menyusun Laporan Keuangan pada Koperasi Pimpinan Daerah Aisiyah Gresik - Tumirin Tumirin; Mu'minatus Sholichah; Djoko Soelistya (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2022)
Cooperatives are business entities consisting of individuals or legal entities that carry out their activities based on the cooperative principle as a people's economic movement based on the principle of kinship. The purpose of Community Service is to develop and provide assistance to application programs for the preparation of financial reports. The application for preparing financial reports is made based on the Microsoft Excel application. Assistance is carried out by training certain operators or officers appointed by the cooperative management. The financial problems of small and medium enterprises and cooperatives can be minimized by preparing accrual-based financial reports. Accrual-based transactions will record all transactions when they occur, even though they are not directly related to cash. Sales and purchase transactions on credit will be recorded immediately when they occur. Thus, the financial condition becomes more orderly and orderly, and this is what happened at the Bueka Assakinah Gresik Cooperative, thus requiring assistance in preparing financial reports. The approach method used in solving partner problems is to conduct an initial survey to find out existing problems, which is then followed by training. And the guidance is given to the partners of the Bueka Assakinah Gresik Cooperative by providing training, especially in the preparation of financial reports, using Microsoft Excel-based programs. The results of the training provide benefits (1) Partners are able to compile financial reports, especially for the Bueka Assakinah Gresik cooperative, (2) Partners are able to read and analyze financial reports that explain financial conditions at a certain time, (3) Problems being faced can be solved, (4 ) Partners are able to understand the importance of financial reports for an institution.